2006
DOI: 10.1007/s00125-006-0226-3
|View full text |Cite
|
Sign up to set email alerts
|

Ghrelin prevents development of diabetes at adult age in streptozotocin-treated newborn rats

Abstract: Aims/hypothesis: Ghrelin, a stomach-derived hormone, functions in multiple biological processes, including glucose metabolism and cellular differentiation and proliferation. In this study, we examined whether early treatment with ghrelin can regenerate beta cells of the pancreas in an animal model of diabetes mellitus, the n0-STZ model, in which neonatal rats are injected with streptozotocin (STZ) at birth.Methods: Following administration of ghrelin to n0-STZ rats from postnatal days 2 to 8, we examined beta … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
64
1
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(72 citation statements)
references
References 40 publications
6
64
1
1
Order By: Relevance
“…In our experimental model, diabetic rats treated with ghrelin did not gain significantly more weight than diabetic rats administered saline. In agreement with our data, although a marked increase in body weight gain is reported in control rats treated with ghrelin (Dembinski et al, 2005;Nakazato et al, 2001;Strassburg et al, 2008), this effect has not always been found in animals suffering from catabolic diseases such as cancer, colitits or diabetes (de Smet et al, 2009;Irako et al, 2006). Thus, the lack of significant weight gain in response to ghrelin could be due to the state of catabolism and extreme weight loss of the diabetic rats.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In our experimental model, diabetic rats treated with ghrelin did not gain significantly more weight than diabetic rats administered saline. In agreement with our data, although a marked increase in body weight gain is reported in control rats treated with ghrelin (Dembinski et al, 2005;Nakazato et al, 2001;Strassburg et al, 2008), this effect has not always been found in animals suffering from catabolic diseases such as cancer, colitits or diabetes (de Smet et al, 2009;Irako et al, 2006). Thus, the lack of significant weight gain in response to ghrelin could be due to the state of catabolism and extreme weight loss of the diabetic rats.…”
Section: Discussionsupporting
confidence: 92%
“…Increased apoptosis of lactotrophs may underlie, at least in part, the reduction in circulating PRL concentrations in poorly controlled diabetic patients or animals (Arroba et al, 2003;Boujon et al, 1995;Ikawa et al, 1992;Iranmanesh et al, 1990;Mera et al, 2007;Steger et al, 1989;Ostrom et al, 1993). This decrease in PRL could result in the reduced or delayed milk production observed in some diabetic women (Hartmann and Cregan, 2001;Neubauer et al 1990Neubauer et al , 1993Neville et al, 1988) and streptozotocin-induced diabetic rats (Ikawa et al, 1992;Lau et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…The production of ghrelin in a prominent endocrine cell population in the fetal pancreas suggests a potential role in islet development. Interestingly, in this context, ghrelin has recently been reported to promote proliferation and cell growth, and also to inhibit apoptosis of pancreatic beta cells and human islets [27,28]. Therefore, one function of ghrelin in the developing pancreas could be to promote cell growth and maturation locally.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is in agreement with the hypothesis of the involvement of acylated ghrelin in the hyperphagia and weight gain of type 1 diabetes after the onset of the disease. It has been reported that exogenous administration of acylated ghrelin ameliorates glucose metabolism in a neonate streptozotocin-induced diabetic rat model through enhancement of cell proliferation (Irako et al 2006) and protective effects against the pro-oxidant damage of diabetes (Turk et al 2012). In a rat model in which ghrelin and GOAT genes are overexpressed in pancreatic b cells under the control of the rat insulin II promoter, the serum insulin levels, pancreatic insulin mRNA expression, and b-cell numbers in islets are increased (Bando et al 2013), suggesting that acylated ghrelin can directly stimulate b-cell proliferation in vivo after islet injury even without its orexigenic or GH-stimulating activities.…”
Section: Type 1 Diabetesmentioning
confidence: 99%